The incidence and microbiological profile of surgical site infections following internal fixation of closed and open fractures - Priscila Rosalba Oliveira; Vladimir Cordeiro Carvalho; Cassia da Silva Felix; Adriana Pereira de Paula; Jorge Santos-Silva; Ana Lucia Lei Munhoz Lima (Revista Brasileira de Ortopedia, 2016)
ABSTRACT OBJECTIVE: To evaluate the incidence and microbiological profile of surgical site infections (SSIs) associated with internal fixation of fractures and to compare differences in the SSIs observed among patients with closed and open fractures. METHODS: Retrospective study. Analyzed data included information from all patients who underwent surgery for fixation of closed or open fractures from January 2005 to December 2012 and remained outpatients for at least one year following surgery. Incidence of surgical site infection (SSI) was compared between patients with closed and open infection, as well as polymicrobial infection and infection related to Gram-negative bacilli (GNB). Cumulative antibiograms were performed to describe microbiological profiles. RESULTS: Overall incidence of SSI was 6%. This incidence was significantly higher among patients with open fractures (14.7%) than among patients with closed fractures (4.2%). The proportions of patients with polymicrobial infections and infections due to GNB were also significantly higher among patients with open fractures. Staphylococcus aureus and coagulase-negative Staphylococcus (CoNS) species were the primary infectious agents isolated from both groups. The overall incidence of MRSA (methicillin-resistant S. aureus) was 72%. A. baumannii was the predominant GNB isolate recovered from patients with open fractures and P. aeruginosa was the most frequent isolate recovered from patients with closed fractures, both exhibited low rates of susceptibility to carbapenems. CONCLUSIONS: Incidence of SSIs related to the internal fixation of fractures was significantly higher among patients with open fractures, indicating that an open fracture can be a risk factor for infection. Among the bacterial isolates, S. aureus (with a high prevalence of MRSA) and CoNS species were most prevalent. A. baumannii and P. aeruginosa isolates underscored the low rate of susceptibility to carbapenems that was observed in the present study.